2016
DOI: 10.1136/gutjnl-2015-310500
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbial profile in patients with primary sclerosing cholangitis is distinct from patients with ulcerative colitis without biliary disease and healthy controls

Abstract: Patients with PSC exhibited a gut microbial signature distinct from both HC and UC without liver disease, but similar in PSC with and without IBD. The genus, which is also associated with other chronic inflammatory and fibrotic conditions, was enriched in PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
317
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 342 publications
(356 citation statements)
references
References 60 publications
25
317
2
2
Order By: Relevance
“…An increased abundance of Enterococcus was associated with increased levels of serum alkaline phosphatase. Similar findings were reported by Kummen et al [33] , who found that the abundance of the genus Veillonella was markedly increased in PSC compared to healthy controls and patients with ulcerative colitis. In our own study, we found a distinctive population of mucosa-adherent bacteria in patients with PSC-IBD, showing significant increases in Escherichia, Lachnospiraceae and Megasphera along with a reduced abundance of Prevotella and Roseburia and a near-absence of Bacteroides [34] .…”
Section: Primary Sclerosing Cholangitissupporting
confidence: 79%
“…An increased abundance of Enterococcus was associated with increased levels of serum alkaline phosphatase. Similar findings were reported by Kummen et al [33] , who found that the abundance of the genus Veillonella was markedly increased in PSC compared to healthy controls and patients with ulcerative colitis. In our own study, we found a distinctive population of mucosa-adherent bacteria in patients with PSC-IBD, showing significant increases in Escherichia, Lachnospiraceae and Megasphera along with a reduced abundance of Prevotella and Roseburia and a near-absence of Bacteroides [34] .…”
Section: Primary Sclerosing Cholangitissupporting
confidence: 79%
“…Recurrent urinary tract infections are a risk factor for the development of PBC 34 . Veillonella genus has recently been associated with PSC and recurrent CD 13 35 . Veillonella was also found in severe inflammatory conditions including endocarditis and cystic fibrosis 36 37.…”
Section: Discussionmentioning
confidence: 99%
“…Primary sclerosing cholangitis (PSC) is commonly observed in patients with IBD and recent studies have investigated the gut microbiome in this disorder 61. Here, 16S rRNA gene sequencing performed in 85 patients with PSC demonstrated that such patients independent of the presence of IBD had a reduced bacterial diversity compared with healthy controls.…”
Section: Primary Sclerosing Cholangitis and Microbiotamentioning
confidence: 94%